Perdón y reconciliación?: legitimidad del proceso de paz con los grupos paramilitares / How pardon and reconciliation?: legitimacy of the peace talks with paramilitary armed groups (2005)
EI presente escrito monográfico, es producto de una investigación en la que se pretende establecer la legitimidad del actual proceso de negociación entre el gobierno y los grupos paramilitares. La metodología empleada fue el análisis de las posiciones discursivas de distintos actores sociales frente al actual proceso. La sostenibilidad política, jurídica y social de todo proceso de paz, descansa en su legitimidad, es decir en la estimación de validez que pueda tener para los miembros de una sociedad a partir de lo que se considera justo y necesario. EI proceso de paz con los grupos paramilitares es considerado valido, por ser necesario socialmente. Sin embargo, la negociación, por cuestiones procedimentales(cese al fuego, verificación, apoyo internacional, etc.) y sustanciales (diálogo con paramilitares narcotraficantes y elusión de la justicia), no es aceptada social mente; se considera injusta. Ética y políticamente, la sociedad colombiana se encuentra ante el dilema que supone la necesidad de detener a uno de los actores armados mas violentos del país (los paramilitares), y la injusticia de aceptar ciertas condiciones que impone el proceso y que ciertamente conducirán a la impunidad (negociar con narcotraficantes y hacer concesiones en cuanto a la justicia). / Abstract. The following monograph is an enquire about the legitimacy of the current peace process and talks held by the Columbian Government and the Illegal Paramilitary Militias. The methodological approach used, implies the analysis of opposing or different discursive standpoints of the various social actors involved in the current process. Legitimacy, stands as an important starting point in order to validate the political, legal and social sustainability of the process; that is, if the process is perceived as fair and necessary among the members of a society it will be considered valid. Assuming the peace talks are valid due to being socially necessary, we find nevertheless that the wholeness of the validity is not achieved, because of procedural vices on the one hand -cease fire, verification of compliance, international support on either side, etc.- and substantial problems on the other - disregarding the fact that tied to the militias the financial support comes from drug trafficking, what makes them drug lords as well, and waving the criminal actions (i.e. slaughters and massacres) negotiations thus hold a load of social rejection, making the process unfair. Ethically and politically, Columbian society faces a dilemma that implies the necessity of stopping one of the most deadly of the armed factions (i.e. the paramilitaries), and the injustice of accepting certain conditions the process demands which would ultimately lead to impunity, by negotiating with narcotic traffickers and making concessions about justice.